COL6A1 gene and Ironman triathlon performance - O'Connell, K.; Posthumus, M.; Collins, M. (International Journal of Sports Medicine, 2011)
Mutations in the type VI collagen gene (COL6A1) cause myopathy and muscle weakness. In addition, COL6A1 knockout mice were shown to have impaired running performance and reduced muscle strength. The COL6A1 rs35796750 polymorphism (IVS32-29 T/C) has been associated with complex phenotypes. The aim of this study was therefore to determine if this polymorphism is associated with performance during the 226 km Ironman triathlon. Participants (n=661) were recruited during 4 South African Ironman triathlons. Finishing times for the 3.8 km swim, 180 km bike, 42.2 km run, and overall race were provided by the race organisers. All participants were genotyped for the COL6A1 rs35796750 polymorphism. Participants with the COL6A1 TT genotype were significantly faster during the bike (p=0.014) and overall race (p=0.030). When participants were grouped into fast, middle and slow bike finishing time tertiles, there was a significant linear trend for the TT genotype (Fast: TT=35.7%; Middle: TT=29.0%; Slow: TT=23.8%; p=0.008). No significant genotype frequency differences were observed for the swim or run of the triathlon. In conclusion, the COL6A1 gene is therefore a potential marker for endurance cycling performance. These effects may be mediated through changes to the composition of type VI collagen containing tissues, such as muscle and tendon.